1978
DOI: 10.1530/jrf.0.0540447
|View full text |Cite
|
Sign up to set email alerts
|

Milk progesterone levels in relation to conception, repeat breeding and factors influencing acyclicity in dairy cows

Abstract: Summary. Milk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
122
3
2

Year Published

1980
1980
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(145 citation statements)
references
References 40 publications
18
122
3
2
Order By: Relevance
“…A number of studies have reported lower P4 in non-pregnant than pregnant cows, whereas, other studies reported no relationship between post-AI P4 and fertility (Bulman and Lamming, 1978;Larson et al, 1997;Mann and Lamming, 1999;Gumen et al, 2003;Stronge et al, 2005;Lonergan et al, 2007;Morris and Diskin, 2008). More extensive logistic regression modeling demonstrated a relationship in dairy cows between P/AI with circulating P4 on days 5, 6 and 7 after AI or with rate of P4 increase after AI (Stronge et al, 2005).…”
Section: Importance Of High P4 After Aimentioning
confidence: 99%
“…A number of studies have reported lower P4 in non-pregnant than pregnant cows, whereas, other studies reported no relationship between post-AI P4 and fertility (Bulman and Lamming, 1978;Larson et al, 1997;Mann and Lamming, 1999;Gumen et al, 2003;Stronge et al, 2005;Lonergan et al, 2007;Morris and Diskin, 2008). More extensive logistic regression modeling demonstrated a relationship in dairy cows between P/AI with circulating P4 on days 5, 6 and 7 after AI or with rate of P4 increase after AI (Stronge et al, 2005).…”
Section: Importance Of High P4 After Aimentioning
confidence: 99%
“…Factors contributing to LH pulse frequency in early postpartum dairy cows In dairy cows, the major factors affecting resumption of ovulation include BCS and energy balance (yield and dry matter intake), parity, season and disease (Bulman and Lamming, 1978;Beam and Butler, 1997;Opsomer et al, 2000;Wathes et al, 2007). Energy intake, BCS and milk yield interact to affect energy balance in dairy cows.…”
Section: Anovulatory Anoestrusmentioning
confidence: 99%
“…Many more studies have looked at the association between the concentration of systemic progesterone in the cycle following insemination and embryo loss; however, the findings have been equivocal with some studies reporting a positive association (Ahmad et al, 1996;Starbuck et al, 2001) while others reported no association (Bulman and Lamming, 1978;Lamming et al, 1989). The inconsistencies in some of the earlier studies may have arisen because invariably they compared the mean concentration of progesterone between cows that conceived and those that did not.…”
Section: Progesterone and Embryo Lossmentioning
confidence: 99%